Testis tumor associated to microlithiasis - Lisieux Eyer de Jesus; Felipe Maciel; Andrea Lima C. Monnerat; Marcia Antunes Fernandes; Samuel Dekermache (Sociedade de Pediatria de São Paulo, 2013)
OBJECTIVE: To discuss the relationship between testicular microlithiasis and testis tumors in children and to consider the chances of testis preserving surgery in specific cases. CASE DESCRIPTION: Pre-adolescent presenting testicular microlithiasis and a larger left testis, corresponding to a cystic testicular tumor. The tumor was excised, with ipsilateral testis preservation. Histology diagnosed a testis dermoid tumor. COMMENTS: The relationship between testis tumors and testicular microlithiasis is ill defined in children. Pediatric urologists need to develop specific follow-up protocols for pre-pubertal children.